The Madams - Wanner, Zukiswa (Paivapo Publishing, 2018)
'I am admitting defeat to my hectic schedule. I am giving in to something that I thought I would never do. I'm going to hire a maid.'' And not just any maid... When Thandi decides she's done with being a Superwomom to her five year old son, a Superslut to her man, and a Superwoman to her staff at the tourism board, she realises she needs to concede to the great South African bourgeois accessory: a maid. And since she doesn't have the heart to boss a 'sister' about in her own home - and would love to see the look on her best friends' faces - Its going to be a white maid...
Keywords: Fiction